SwissFEL: The Swiss X-ray Free Electron Laser - Christopher J. Milne; Thomas Schietinger; Masamitsu Aiba; Arturo Alarcon; Jürgen Alex; Alexander Anghel; Vladimir Arsov; Carl Beard; Paul Beaud; Simona Bettoni; Markus Bopp; Helge Brands; et al. (Applied Sciences, 2017)
The SwissFEL X-ray Free Electron Laser (XFEL) facility started construction at the Paul Scherrer Institute (Villigen, Switzerland) in 2013 and will be ready to accept its first users in 2018 on the Aramis hard X-ray branch. In the following sections we will summarize the various aspects of the project, including the design of the soft and hard X-ray branches of the accelerator, the results of SwissFEL performance simulations, details of the photon beamlines and experimental stations, and our first commissioning results.